PANTI ASUHAN ANAK DI KOTA PONTIANAK DENGAN PENDEKATAN DESAIN INKLUSIF - Mardiyanto Mardiyanto; Tri Wibowo Caesariadi; Uray Fery Andi (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Institutions such as orphanages are needed throughout Indonesia for the welfare and protection of children's rights. Pontianak City has the largest population in West Kalimantan Province with the welfare and protection of children's rights cannot be said to be feasible. This design uses an inclusive design approach. Inclusive design is a design approach that focuses on meeting the needs of children both socially and physically, it requires a facility and product for everyone (as users) in general, without physical limitations, age range and gender. The purpose of this design is to design an orphanage that can meet the needs of orphans and children with special needs. The design is carried out using the Design Thinking method, namely by collecting ideas from various literatures to obtain a solution. The results of this design are an orphanage that can accommodate the needs of orphanage children in the form of buildings with rooms arranged in a zoning manner, the shape of the building is made thin to maximize natural lighting and ventilation, the park as an open space for children's social activities, and self-development facilities for children in the form of recreation rooms and hydroponic gardens. The orphanage also uses room facilities with railings, guiding blocks, braille letters, efficient furniture for everyone to use, including for children with disabilities with an inclusive design approach.